The Urgency Regulation Prohibition of Social Commerce in Indonesia From The Perspective Maslahah Mursalah - Oktavia, Dian Novyta; Batubara, Chuzaimah (JURNAL USM LAW REVIEW, 2024)
This research aims to determine the importance of social commerce regulations, explore the development and implementation of these regulations in Indonesia, and understand Maslahah Mursalah's views on these regulations. The current rapid growth of digital technology has driven great progress in various scientific disciplines, particularly in the economic sector, where business actors, especially MSMEs, are starting to participate in the e-commerce space. With the emergence of online trading trends that use social media as the main platform (social commerce), government awareness of the growth potential of e-commerce has encouraged the government to adopt strict and enforceable regulations. This scientific study uses normative juridical research methodology, specifically focussing on secondary data sources. These sources include primary legal materials, such as statutory regulations (legislative approach), and secondary legal sources accessed through library sources. The study revealed that the Minister of Trade, Zulkifli Hasan, has issued new regulations, namely Minister of Home Affairs Regulation (Permendagri) Number 31 of 2023 concerning Licensing, Advertising, Development, and Supervision of Trading Business Entities via Electronic Systems. This law aims to help Micro, Small, and Medium Enterprises (MSMEs), clarify social commerce operations, and foster a strong e-commerce ecosystem. However, some view the government's issuance of this regulation as lacking substance and haste. Mursalah's problem is that government regulations, specifically Minister of Trade Regulation Number 31 of 2023, only address a few aspects of enhancing human welfare, particularly for commercial actors.
Keywords: Maslahah Mursalah; Regulation; Social Commerce